SUPPLY AND DEMAND AT TRADITIONAL MARKET IN SURABAYA - Mahargiono, Pontjo; Oetomo, Hening; Cahyono, Krido (PEOPLE: International Journal of Social Sciences, 2017)
This research is aimed to answer the research question i.e. how do the supply and demand of traditional market at Soponyono and Paing market in Rungkut sub district Surabaya. Soponyono market is a traditional market which is located in Kalirungkut sub district while Paing market is located in Rungkut kidul sub district. The supply factors which are studied in this research are the number of market, the number of mini market, the number of restaurant and the number of mini market within 1000 meters radius. The demand factors in this research are studied by using the number of offices, the number of schools, the number of financial institution and the number of house of worship within 1000 meters radius. The calculation of the value of demand and supply has been conducted by using Index model which consist of 3 steps. First, the standardization of the absolute value of the number of objects within 1000 meters radius, second, the determination of the value of supply or demand of each indicator, third, the value of the standardization. The result shows that the demand value either at Soponyono market or even at Paing market is good and higher than the supply value, therefore it is possible to build new market within 1000 meters radius from the market location